Earth unaware : the First Formic War - Card, Orson Scott (Card, Orson Scott. Formic Wars, 2012)
The mining ship El Cavador, beyond Pluto, detects a fast-moving incoming object headed toward Earth. The crew decides it's probably not important, but they're wrong: it represents the opening wave of the first Formic War.